2015
DOI: 10.1186/s12887-015-0462-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of weaning strategies for preterm infants on nasal continuous positive airway pressure

Abstract: BackgroundThe optimal strategy for weaning very preterm infants from nasal continuous positive airway pressure (NCPAP) is unclear. Reported strategies include weaning NCPAP to a predefined pressure then trialling stopping completely (abrupt wean); alternate periods of increased time off NCPAP whilst reducing time on until the infant is completely weaned (gradual wean); and using high flow nasal cannula (HFNC) to assist the weaning process. The aim of this study was to determine the optimal weaning from NCPAP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 22 publications
3
52
0
Order By: Relevance
“…To date, eleven respective randomized controlled trials can be found in the literature [2,3,13,27,29]. All these trials comprise a rather small number of participants.…”
Section: Weaning Strategies -Scientific Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…To date, eleven respective randomized controlled trials can be found in the literature [2,3,13,27,29]. All these trials comprise a rather small number of participants.…”
Section: Weaning Strategies -Scientific Evidencementioning
confidence: 99%
“…Application of the CICADA method not only shortened the duration of nCPAP, but was also associated with less chronic lung disease, less time on supplemental oxygen and a shorter duration of overall hospital stay [5,30]. The trials of Singh et al [21], Soe et al [22] and Tang et al [29] also reported a shorter duration of nCPAP when weaning was abruptly stopped. Nair et al [17] found no differences, when comparing these strategies.…”
Section: Weaning Strategies -Scientific Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Four RCTs have examined nHF as a strategy for weaning from CPAP, with conflicting effects seen on the duration of supplemental oxygen and respiratory support . Two studies found no difference in outcome when weaning directly from CPAP was compared with changing to nHF.…”
Section: Indications For Nhf Therapymentioning
confidence: 99%
“…Four RCTs have examined nHF as a strategy for weaning from CPAP, with conflicting effects seen on the duration of supplemental oxygen and respiratory support . Two studies found no difference in outcome when weaning directly from CPAP was compared with changing to nHF. The third study found that using nHF to wean from CPAP resulted in more days of supplemental oxygen and respiratory support, and a fourth study found the reverse to be true .…”
Section: Indications For Nhf Therapymentioning
confidence: 99%